Prevalence of subclinical retinal ischemia in patients with cardiovascular disease – a hypothesis driven study. (March 2021) - Long, Christopher P.; Chan, Alison X.; Bakhoum, Christine Y.; Toomey, Christopher B.; Madala, Samantha; Garg, Anupam K.; Freeman, William R; Goldbaum, Michael H.; DeMaria, Anthony N.; Bakhoum, Mathieu F.
Abstract: Background: Cardiovascular disease is the leading cause of mortality and disability worldwide. A noninvasive test that can detect underlying cardiovascular disease has the potential to identify patients at risk prior to the occurrence of adverse cardiovascular events. We sought to determine whether an easily observed imaging finding indicative of retinal ischemia, which we term ' retinal ischemic perivascular lesions' (RIPLs), could serve as a biomarker for cardiovascular disease. Methods: We reviewed optical coherence tomography (OCT) scans of individuals, with no underlying retinal pathology, obtained at UC San Diego Health from July 2014 to July 2019. We identified 84 patients with documented cardiovascular disease and 76 healthy controls. OCT scans were assessed for evidence of RIPLs. In addition, the 10-year atherosclerotic cardiovascular disease (ASCVD) risk calculator was used to risk-stratify the subjects into four different categories. Findings: Patients with documented cardiovascular disease had higher number of RIPLs compared to healthy controls (2.8 vs 0.8, p < 0.001). After adjusting for age, sex, smoking history, systolic blood pressure and triglycerides, cholesterol and hemoglobin A1C levels, each RIPL was associated with an odds ratio of having cardiovascular disease of 1·60 (1.09–2>37). The number of RIPLs in individuals with intermediate and high 10-year ASCVD risk scores was higher than in those with low ASCVD risk scores (1.7 vs 0.64, p = 0.02 and 2.9 vs 0.64, p 0.002, respectively). Interpretation: The presence of RIPLs, which are anatomical markers of prior retinal ischemic infarcts, is suggestive of coexisting cardiovascular disease. RIPLs detection, obtained from routine retinal scans, may thus provide an additional biomarker to identify patients at risk of developing adverse cardiovascular events. Funding: None.